Case theory: Strategic oral litigation in virtual times - Abanto Revilla, César (2021)
This essay reviews the importance of the case theory in the development of the new labor process. It highlights the relevance of orality as a technique that seeks to replace the written model. It also shows thecomplications in the development of its application, which were caused by the accelerated judicial virtuality as a result of the COVID-19 pandemic.